Trees of tales: A playful reading application for Arabic children - Alaamri, F.; Greuter, S.; Walz, Steffen (2014)
In this study, we have developed a playful interactive reading and storytellng application called ‘Trees of Tales’. The tablet application was designed to motivate Arabic children to read more for pleasure. ‘Trees of Tales’ was evaluated with 18 primary school children in Oman to investigate its effectiveness as an enjoyable reading tool. To assess the impact on usability and the children’s experience of fun and reading preference, we conducted three reading sessions in which all participants read stories from ‘Trees of Tales’, non-interactive e-books and conventional printed books. This paper describes the design of the ‘Trees of Tales’ application as well as the results obtained with the ‘fun toolkit’.